Micro Financial Sharia Non-bank Strategic Analysis: a Study at BMT Beringharjo, Yogyakarta - Marissa Grace Haque; Nurjaya Nurjaya; Azhar Affandi; Heri Erlangga; Denok Sunarsi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Prior to the 1998 economic downfall, and in ten years after in 2008, BMT (Baitul Maal wa Tamwil) proofed the endurance to remain stable. From those external factors, strived the company very hard hard to sustain its business, as well as to formulate a better strategy to its competitive advantage. The research begins with the internal and external analysis, using a SWOT Analysis. The results shows its business strength and its market penetration, lies in its company’s human development. Through the IE Matrix, founds BMT Beringharjo competitive position in Quadrant or cell IV Matrix IE, with growth strategy through horizontal integration concentration. Based on its position of: (1) competition; (2) strength; (3) weakness; (4) opportunity; (5) threats. Enriched with strategy of: (1) market penetration; (2) market development; as well as (3) horizontal integration strategy to the creative innovation strategy is inevitable to remain exist and gain more success.